Learning Methods on Environmental Education to Improve Pre-Service Teachers Environmental Literacy - Febrianawati Yusup; Istiqamah Istiqamah; Khairunnisa Khairunnisa (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
Environmental damage is still happening. The wrong human perspective on the environment that causes this damage continues. Only humans with environmental literacy can solve environmental problems. Environmental education is seen as the most effective way to educate people about environmental issues at all levels of education. Teachers are the front line in the success of education. However, there is no special program to prepare pre-service teachers environmental literacy on teachers through environmental education. A literature review is used to explore which learning methods are effective in improving attitudes, knowledge, and environmental behaviors for pre-service teacher students in scientific articles published from 2011 to 2021. Scientific articles were source from Google Scholar, ERIC, EBSCOhost, SAGE, Taylor and Francis, Sciencedirect, JSTOR, and Proceeding online. Twenty-one articles were selected from predetermined criteria. From the results of the analysis, learning methods in environmental education that are effectively used to improve the environmental literacy of pre-service teacher students include Environmental Education courses, Outdoor-based learning, Project Based Learning (PjBL), Problem Based Learning (PBL), Science, Technology learning, Engineering, and Mathematics (STEM), Constructivist Learning, Guided Inquiry, Demonstration, Environmental and Sustainability Education (ESE), Pedagogical Experiments, 3R-oriented learning, Contextual Approach based on local wisdom, environmental education based on transformational learning theory, and Integration of drama, film, and educational videos. The choice of method must still be adjusted to the learning material.